2022
DOI: 10.1108/shr-11-2022-0061
|View full text |Cite
|
Sign up to set email alerts
|

Differences in preferences for appreciation across various work settings

Abstract: Purpose Previous research has documented the distribution of preferences of various appreciation languages by employees in general work settings. This paper aims to explore if employee preferences for appreciation vary across different types of workplace settings. Design/methodology/approach The Motivating By Appreciation Inventory assesses individuals’ preferred ways of receiving appreciation from their workplace colleagues, determining each person’s primary language of appreciation in one of four appreciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The distribution of the primary languages of appreciation as determined by the MBA Inventory for this group was compared with the incidence rate across the general population (White, 2023b). As can be seen in Table 1, although the relative frequencies of each appreciation language in this group are slightly different than the distribution found in the general population, the overall pattern is similar.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of the primary languages of appreciation as determined by the MBA Inventory for this group was compared with the incidence rate across the general population (White, 2023b). As can be seen in Table 1, although the relative frequencies of each appreciation language in this group are slightly different than the distribution found in the general population, the overall pattern is similar.…”
Section: Methodsmentioning
confidence: 99%
“…Research (White, 2017) has shown that not everyone feels appreciated in the same ways and that differences in preferences occur across age groups (White, 2018; White and George, 2022) and occupational settings (White, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that individuals prefer to be shown appreciation in various ways (White, 2017). Additionally, differences in preferences occur across age groups (White, 2018a(White, , 2018bWhite and George, 2022), occupational settings (White, 2023a) and whether the employees work primarily remotely or onsite (White, 2021).…”
mentioning
confidence: 99%